EMPIRICAL EVIDENCES ON SOCIAL EMPOWERMENT OF WOMEN THROUGH SHGS IN INDIA (A STUDY WITH SPECIAL REFERENCES TO SATTUR TALUK) - PREMA, S.; NACHIAR, B.KOTHAI (International Journal of Psychosocial Rehabilitation, 2020)
Women empowerment measures (SHG) initiated by the Government of India is more dominant and fruitful success. SHGs have been emerged as a powerful instrument in order to alleviate poverty and for the empowerment of women in the rural economy. This study aims to analyse the nature of social empowerment women have achieved through their participation in SHG activities. The study has adopted convenience sampling techniques for collection of primary data i.e., from the members of SHGs at Sattur Taluk. Based on small sampling technique thirty respondents were chosen as sample population i.e., 30 members of SHGs in Sattur taluk. The empirical results of the study revealed that the socio-economic status of the respondents has been improved after joining in Self Help Groups (SHGs). Majority of the respondents have restructured their house with more facilities, have bought more household utensils and have got drinking water connection in house after joining in SHGs. Most of the sample subjects have taken insurance policy after joining in Self Help Groups (SHGs), opened savings account in banks and post office and have stated that they owe gold or investment and other kind of savings like chits funds, asset holdings etc.